Multi-Informant Assessment of Bullying in Austrian Schools - Paljakka, Antonia; Schwab, Susanne; Zurbriggen, Carmen L. A. (Frontiers in Education, 2021)
This study explores the agreement of bullying reports from different perspectives. Nominations and (self and peer) ratings of 721 students (50.5% boys, 49.5% girls, aged 9–11), 46 teachers (91.3% female, 8.7% male; Mage = 40.28 years, SDage = 1.6, teaching experience between 2 and 36 years, Mexperience = 15.16, SDexperience = 1.68), 439 mothers, and 363 fathers were analyzed. Measures included a modified version of the Revised Olweus Bully/Victim questionnaire (OBVQ) as well as nomination items, with variables on physical and relational bullying and victimization, and frequency of experience. For descriptive analyses, group comparisons and correlations were performed and to test the dimensional structure of the modified Revised OBVQ we fitted a categorical confirmatory factor analysis (CCFA) for all four raters. To estimate the degree of agreement between the four raters, we applied a simple multitrait-multimethod (MTMM) analysis in a CCFA framework. Results indicated that teachers are more likely to recognize physical bullying than relational bullying. Significant gender effects were found, with more frequent nominations for boys and a larger gender effect for physical bullying. Overall, teachers reported the highest levels of bullying, and students reported significantly higher levels of victimization compared to the other raters. In terms of bullying, the MTMM model revealed a slightly higher agreement between students and parents than between students and teachers. The findings further indicate a tendency for lower agreement between student and adult reports than among adults’ reports. The notably high agreement between the ratings of mothers and fathers for both bullying and victimization supports the research strategy to include only one parent. Although bullying is assessed from various perspectives, the study does not provide prevalence estimates of bullying in Austria.